2018
DOI: 10.1016/j.hpb.2017.08.032
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter outcomes of robotic reconstruction during the early learning curve for minimally-invasive pancreaticoduodenectomy

Abstract: These multicenter data during the early learning curve for RA-MIPD do not demonstrate excess anastomotic morbidity compared to open. Further studies are required to determine whether surgeon proficiency and evolving technique improve anastomotic outcomes compared to open.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
46
1
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(49 citation statements)
references
References 56 publications
0
46
1
2
Order By: Relevance
“…Several studies have suggested that RPD is associated with a shorter learning curve and decreased open conversion rate compared to LPD, and is a valuable addition to the armamentarium of surgeons embarking on MIPD. The recent multi‐centre study from the United States, which looked at robotic reconstruction during the early learning curve, compared with the open technique showed no difference in anastomotic complications, suggesting that RPD can be adopted safely even during the learning phase. This was unlike the results of several studies on LDP, which suggested that there was an increase in morbidity such as pancreatic fistula over the open approach during the learning curve.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have suggested that RPD is associated with a shorter learning curve and decreased open conversion rate compared to LPD, and is a valuable addition to the armamentarium of surgeons embarking on MIPD. The recent multi‐centre study from the United States, which looked at robotic reconstruction during the early learning curve, compared with the open technique showed no difference in anastomotic complications, suggesting that RPD can be adopted safely even during the learning phase. This was unlike the results of several studies on LDP, which suggested that there was an increase in morbidity such as pancreatic fistula over the open approach during the learning curve.…”
Section: Discussionmentioning
confidence: 99%
“…There was no difference in the overall morbidity rate of RPD compared to LPD . Another multicentre study from the United States demonstrated that RPD could be adopted safely with similar overall and anastomotic complications compared to the open approach even during the early learning phase . In contrast, a study on LPD demonstrated that it was associated with a higher morbidity rate compared to the open approach .…”
Section: Discussionmentioning
confidence: 98%
“…Although the safety and benefits have been shown in many studies, minimally invasive hepato‐pancreato‐biliary surgery has not been widely adopted for major operations including hemi‐hepatectomy and pancreatoduodenectomy procedures . The steep learning curve of hepatic or pancreatic resections may cause the reluctances to use minimally invasive techniques in this field.…”
Section: Discussionmentioning
confidence: 99%
“…Robotic gastrectomy has been shown to be equally safe in oncologic terms with additional benefits of less blood loss and decreased hospi- Although the safety and benefits have been shown in many studies, 11,31 minimally invasive hepato-pancreato-biliary surgery has not been widely adopted for major operations including hemi-hepatectomy and pancreatoduodenectomy procedures. 32 The steep learning curve of hepatic 33 or pancreatic 34 resections may cause the reluctances to use minimally invasive techniques in this field. In Turkey, utilisation of the robots in hepatic or pancreatic resections seems parallel to general worldwide trend.…”
Section: Discussionmentioning
confidence: 99%